A study on SMES propensity in choosing business advisory services: a case in Kota Bharu, Kelantan, Malaysia / Mohd Zainuri Muhammad … [et al.] - Muhammad, Mohd Zainuri; Hussin Bidin, Yeop; Ishak, Ismail; Shaari, Rustam (2008)
As Malaysia steers itself to the rapid pace of the global economy, so too is the government reliance of SME Bank as an important force in sustaining national economic growth. The bank was initially established to be business incubation center with the aim of facilitating financing to entrepreneurs in the small medium industry. However, with the intensity of the global competition, SME Bank has begun to offer business advisory services in areas such as training and development, business operations, research, marketing and product or service strategy. This research is examining the small medium enterprises propensity to choose business advisors in providing assistance and direction in their business. The data was collected from 130 existing clients of the SME bank branch in Kota Bharu, Kelantan. Analysis to establish relationship between variables had shown that perceived benefit, trust, knowledge of service and business advisors skills were significantly considered by these entrepreneurs in selecting the business advisory firms while cost is not considered as a factor in their decision. The finding also showed that perceived benefit is the most important in their decision to appoint the business advisors. As such, SME Bank should highlight the timely contribution of business advisors in furthering the development of the small medium enterprises in Malaysia economic growth.